An investigation of disabled women's perceptions of HIV and AIDS and aspects of sex and sexuality in three South African provinces - Basson, Melanie (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Psychology))--University of Stellenbosch, 2010.